Treatment of limb skin defect with self-made skin distractor - Gao Lei; Li Kai; Zhang Yanlong; Wang Hongrun; Liu Shibo; Wang Yong; Peng Aqin (BMC Musculoskeletal Disorders)
Abstract Objective To investigate the effect of self-made skin distractor in the treatment of limb skin defects. Methods From September 2018 to January 2020, 15 cases of limb skin defects (16 wounds) were treated with self-designed skin distractor, including 13 males and 2 females, with an average age of 42 years (range, 9–73 years). The smallest area of skin defect was 6 cm×3 cm, the largest was 32 cm ×7 cm, with an average of 72.4cm2. The wound healing was observed, complications and the time of use of the distractor were recorded. Results All patients were followed up for 6–12 months with an average of 9.2 months. Of the 16 wounds in 15 patients, 2 wounds were closed in one stage during operation, 13 wounds were delayed in primary closure. A skin incision occurred in 1 case, but the wound closure was not affected; One wound were not closed completely, because the skin was cut by Kirschner wire, and could not be stretched continously. The remaining wounds were closed by skin grafting. Another case also had skin cutting was occurred in another case, but the wound closure was not affected. No skin stretch was terminated due to pain. All wounds were healed. The elasticity and color of the skin on the wound surface were not different from the surrounding skin. The movement of the adjacent joints was basically normal. Conclusion The self-made skin stretcher is simple in structure and easy to use. It provides a reliable and effective method for the treatment of skin defects of limbs.